Sensory preference and acceptability of cabinet-dried candied tomatoes (Lycopersicon esculentum var. Ilocos red) - Ceñidoza, Kristine Joy P.; Azanza, Ma. Patricia V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This study aimed to use sensory evaluation tools to select an acceptable process for cabinet-dried candied tomatoes. Dried candied tomatoes were processed using variable sugar concentrations (20, 25 and 30%) and citric acid concentrations (0.5 and 0.6%) with different cabinet drying temperatures (60, 70 and 80°C). Physico-chemical characteristics of the dried candied tomatoes were investigated. Moisture content and water activity were found to be significantly different although all parameters were lower than fresh Ilocos Red. Preference ranking and consumer acceptance tests showed that product treatment with 25% sugar, 0.5% citric acid and dried at 60°C was the most preferred and acceptable product while the treatment with 20% sugar, 0.5% citric acid and dried at 80°C was the least. Regression analysis revealed that tomato flavor and sourness were the primary predictors for overall acceptability of the dried candied tomatoes. High overall acceptability ratings were associated with high values for tomato flavor and sourness. On the contrary, color and texture have little effect on the overall acceptability of the products. Although sweetness has a definite contribution to overall acceptability, it may be considered as a compliment to the other predictors. Preference ranking and acceptance tests, in conjunction with regression analysis, were found to be effective in selecting an acceptable process for the development of dried candied tomatoes. The use of intensity scaling with principal component analysis is highly recommended for future studies.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Tomatoes -- Philippines